2015
DOI: 10.1152/ajpheart.00623.2015
|View full text |Cite
|
Sign up to set email alerts
|

Leptin decreases heart rate associated with increased ventricular repolarization via its receptor

Abstract: Leptin has been proposed to modulate cardiac electrical properties via ␤-adrenergic receptor activation. The presence of leptin receptors and adipocytes in myocardium raised a question as to whether leptin can directly modulate cardiac electrical properties such as heart rate and QT interval via its receptor. In this work, the role of local direct actions of leptin on heart rate and ventricular repolarization was investigated. We identified the protein expression of leptin receptors at cell surface of sinus no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…ECG system consist of 3 leads vector connected to the signal recording and application system (PowerLab/4SP analog-to-digital converter, AD Instruments, Colorado Springs, CO). A mixture of 2% isoflurane and compressed oxygen was used for anesthesia with flow rate at 2L/min [ 49 , 50 ]. Data of each group were derived from 8 mice.…”
Section: Methodsmentioning
confidence: 99%
“…ECG system consist of 3 leads vector connected to the signal recording and application system (PowerLab/4SP analog-to-digital converter, AD Instruments, Colorado Springs, CO). A mixture of 2% isoflurane and compressed oxygen was used for anesthesia with flow rate at 2L/min [ 49 , 50 ]. Data of each group were derived from 8 mice.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic central leptin infusion in diabetic rats could completely restore cardiac sympathetic tone and reverse HR variability to levels of nondiabetic rats [53] . Lin et al [54] also provided evidence for leptin-induced decrease in HR via leptin receptors being independent of adrenergic receptor stimulation in adult male rats. We revealed that leptin/BMI was related with HRV in CKD patients, SHPT patients with lowest serum leptin levels had increased HRV and circulating leptin/BMI level after PTX.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, although the detailed mechanisms to explain the effect of leptin on the electric properties of the heart are not well described. Lin et al described a stimulant effect on the adrenergic receptors because a high concentration of leptin increases the QT interval, triggering arrhythmias such as premature ventricular bits, sinus pauses, and ventricular tachycardia [ 31 ]. Our results indicate that leptin induces alterations in cardiac performance, probably through upregulation of different calcium channels such as the L-type or Na/Ca translocator, resulting in calcium overload in mitochondria during contractile function and explaining the in vitro sensitization to calcium, but this remains a topic for future research.…”
Section: Discussionmentioning
confidence: 99%